Radiotracers in the Diagnosis of Pain: A Mini Review - Hascalovici, Jacob; Babb, Anthony; Norwood, Braxton A. (Seminars in Musculoskeletal Radiology, 2023)
The diagnosis and understanding of pain is challenging in clinical practice. Assessing pain relies heavily on self-reporting by patients, rendering it inherently subjective. Traditional clinical imaging methods such as computed tomography and magnetic resonance imaging can only detect anatomical abnormalities, offering limited sensitivity and specificity in identifying pain-causing conditions. Radiotracers play a vital role in molecular imaging that aims to identify abnormal biological processes at the cellular level, even in apparently normal anatomical structures. Therefore, molecular imaging is an important area of research as a prospective diagnostic modality for pain-causing pathophysiology. We present a mini review of the current knowledge base regarding radiotracers for identification of pain in vivo. We also describe radiocaine, a novel positron emission tomography imaging agent for sodium channels that has shown great potential for identifying/labeling pain-producing nerves and producing an objectively measurable pain intensity signal.
Keywords: radiotracers; pain; positron emission tomography imaging; single-photon emission computed tomography imaging